Anaemia and low birth weight in Medani, Hospital Sudan - Elhassan, Elhassan M (BioMed Central, 2010)
BACKGROUND: Reducing the incidence of Low birth weight (LBW) neonates by at least one third between 2000 and 2010 is one of the major goals of the United Nations resolution "A World Fit for Children". This was a case-control study conducted between August-October 2009 in Medani Hospital, Sudan to investigate the risk factors for LBW. Cases were mothers who delivered singleton baby < 2500 gm. Controls were mothers delivered singleton baby of ≥ 2500 gm. FINDINGS: Out of 1224 deliveries, 97 (12.6%) of the neonates were LBW deliveries. While maternal socio-demographic characteristics (age, parity and mother education) and anthropometrics measurements were not associated with LBW, lack of antenatal care (OR = 5.9, 95% CI = 1.4-24.4; P = 0.01) and maternal anaemia (OR = 9.0, 95% CI = 3.4-23.8; P < 0.001) were the main risk factor for LBW. CONCLUSION: Thus, more care on antenatal care and nutrition may prevent LBW.